2016
DOI: 10.1371/journal.pone.0156217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Environmental DNA Method for Estimating Distribution and Biomass of Submerged Aquatic Plants

Abstract: The environmental DNA (eDNA) method has increasingly been recognized as a powerful tool for monitoring aquatic animal species; however, its application for monitoring aquatic plants is limited. To evaluate eDNA analysis for estimating the distribution of aquatic plants, we compared its estimated distributions with eDNA analysis, visual observation, and past distribution records for the submerged species Hydrilla verticillata. Moreover, we conducted aquarium experiments using H. verticillata and Egeria densa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…As eDNA methods to date have not been extensively used to monitor aquatic plants (but see Scriver et al 2015;Fujiwara et al 2016), and because plants may not always release detectable amounts of DNA (e.g. Matsuhashi et al 2016) suggesting the use of eDNA methods for plant conservation may still be in its infancy, I only concentrate on animal studies herein (but recognise some key points may be transferable).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As eDNA methods to date have not been extensively used to monitor aquatic plants (but see Scriver et al 2015;Fujiwara et al 2016), and because plants may not always release detectable amounts of DNA (e.g. Matsuhashi et al 2016) suggesting the use of eDNA methods for plant conservation may still be in its infancy, I only concentrate on animal studies herein (but recognise some key points may be transferable).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Detection of aquatic plant eDNA has been scarce in comparison [31]. In the wild it was first demonstrated for Egeria densa and Hydrilla verticillata in small Japanese ponds (83–6000 m 2 ) where the presence of the species was visually confirmed and compared to past distribution records [32, 33]. Another study successfully tested eDNA detection of H .…”
Section: Introductionmentioning
confidence: 99%
“…verticillata in north American rivers and lakes [34] and three studies detected eDNA where the species had not yet been observed [31, 34, 35]. Several laboratory mesocosm experiments have tested the changes in aquatic plant eDNA over time, during and after introduction, and with and without grazers [32–34]. However, to the best of our knowledge, no temporal or spatial studies have yet been conducted in the wild for studying potential seasonal variations and transportation of aquatic plants eDNA.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most promising advances in invasive species surveillance to emerge recently has been environmental DNA (eDNA), or DNA of macrobiota collected and identified from environmental samples (Ficetola et al, 2008;Lodge et al, 2012b). Research to date has consistently found eDNA to be highly sensitive to detection of potentially harmful species at the low population abundances associated with early stages of invasion (e.g., Egan et al, 2015;Smart et al, 2015;Dougherty et al, 2016;Matsuhashi et al, 2016). However, a number of questions related to the application and interpretation of eDNA methods persist and require ongoing research attention (Roussel et al, 2015;Barnes & Turner, 2016).…”
Section: Introductionmentioning
confidence: 99%